2018
DOI: 10.1021/acs.inorgchem.8b01695
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Computational Study of a Pyridylcarbene Fe(II) Complex: Unexpected Effects of fac/mer Isomerism in Metal-to-Ligand Triplet Potential Energy Surfaces

Abstract: The synthesis and the steady-state absorption spectrum of a new pyridine-imidazolylidene Fe(II) complex (Fe-NHC) are presented. A detailed mechanism of the triplet metal-to-ligand charge-transfer states decay is provided on the basis of minimum energy path (MEP) calculations used to connect the lowest-lying singlet, triplet, and quintet state minima. The competition between the different decay pathways involved in the photoresponse is assessed by analyzing the shapes of the obtained potential energy surfaces. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(103 citation statements)
references
References 71 publications
7
96
0
Order By: Relevance
“…Figure S16. Coherently with what observed for fac-C1 and mer-C1, 23 the main coordinate driving the process is the enlargement of the Fe-N1 bond, which has a bond distance of 2.82 Å at the T 1 ( 3 MC) min geometry ( Fig. 4a).…”
Section: Excited-state Computational Studiessupporting
confidence: 72%
See 2 more Smart Citations
“…Figure S16. Coherently with what observed for fac-C1 and mer-C1, 23 the main coordinate driving the process is the enlargement of the Fe-N1 bond, which has a bond distance of 2.82 Å at the T 1 ( 3 MC) min geometry ( Fig. 4a).…”
Section: Excited-state Computational Studiessupporting
confidence: 72%
“…Recently, and to influence the angular strain, we have reported the first example of iron complex with bidentate pyridylcarbene ligands C1. 23 The asymmetric nature of the employed ligand led to different geometrical isomers. In fact, C1 was obtained as a mixture of mostly the meridional (mer) isomer with a concomitant fraction of the facial (fac) isomer in a 14:1 ratio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14,31] Recent computational work by Monaria nd co-workers demonstrated that there could be subtle but important differences in the 3 MLCT deactivation pathways for fac and mer isomers of the same Fe II -carbene complex, and they concluded that FeÀN bond elongation was the key normalc oordinate leading to triplet relaxation. [32] Their work underscores the importance of complete calculation of the potential-energy surfaces to adequately describe excited-state relaxation.…”
Section: Mlct States In Strained Low-spin Complexesmentioning
confidence: 99%
“…The use of a bidentate pyridine-imidazole-derived ligand led to [Fe(mpi) 3 ] 2+ (mpi = 3-methyl-1-(pyridin-2-yl)-imidazol-2-ylidene) which exists in two different isomers with either meridional or facial coordination of the carbene/pyridine moieties (Figure 15) [54]. When synthesized the complex is obtained in a 14:1 mer/fac mixture that is inseparable.…”
Section: Fenhc Complexes With Bidentate Ligandsmentioning
confidence: 99%